ANALYSIS OF THE POTENTIAL AND DEVELOPMENT OF THE GONDANG DAM TOURISM OBJECT AND THE ECONOMIC IMPACT ON THE SURROUNDING COMMUNITY - Istiqomah Arum Annisa; Pranichayudha Rohsulina; Talitha Rahmawati (Journal of Geography Science and Education, 2020)
This study aims to see: Determine the tourism potential of the Gondang Dam. knowing the direction of the development of the Gondang Dam tourism object, knowing the impact of the Gondang Dam on the economic conditions of the surrounding community. This study uses a qualitative descriptive method. The data technique used is through field observations, interviews and documentation. The data analysis techniques were scoring and descriptive. The results of this study are: Gondang Dam is a very potential tourism object as well as the most potential reservoir tourism object of the existing reservoirs in Karanganyar Regency. The Gondang Dam still needs further development directions, including the following aspects: recreation / attractions, accessibility, infrastructure, superior products / distinctive products, and promotional efforts. The economic impact felt by the community after the Gondang dam tends to be positive. Positive impacts: Increasing community income, creating job opportunities, encouraging community creativity. While the negative impacts: Some of the community no longer have land to work on, there are more competitors to open businesses, processed traditional products will be left behind by modern processing, because there are more people.